2004
DOI: 10.1111/j.1526-0968.2004.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Angiotensin Receptor Antagonist, Angiotensin Converting Enzyme Inhibitor, and their Combination on Regression of Left Ventricular Hypertrophy of Diabetes Type 2 Patients on Recent Onset Hemodialysis Therapy

Abstract: Left ventricular hypertrophy (LVH) is frequently found at the initiation of dialysis therapy of diabetic and hypertensive patients, and is highly predictive of future cardiac morbidity and mortality. In patients with hypertension and LVH, both an angiotensin converting enzyme (ACE) inhibitor and an angiotensin type 1 receptor (AT1) antagonist regress LVH. However, it remains controversial whether dual blockade of the renin-angiotensin system will regress LVH in these patients using a combination of ACE inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
(28 reference statements)
0
26
0
Order By: Relevance
“…Although a better response with angiotensin blockers compared to converting enzymes was not observed in another small trial of 33 incident, diabetic hemodialysis patients randomized to enalapril 10 mg daily, losartan 100 mg daily or combination therapy, there was a blood pressure independent benefit of more complete angiotensin blockade. At 1 year, LVH progressively decreased in all 3 groups, but there was an additional 28% reduction in the dual therapy group (P<0.05) 70 despite similar blood pressure reduction. A 3 rd small trial compared imadpril (2.5 mg daily) with placebo in 30 hemodialysis patients.…”
Section: Interventions To Regress Lvhmentioning
confidence: 85%
“…Although a better response with angiotensin blockers compared to converting enzymes was not observed in another small trial of 33 incident, diabetic hemodialysis patients randomized to enalapril 10 mg daily, losartan 100 mg daily or combination therapy, there was a blood pressure independent benefit of more complete angiotensin blockade. At 1 year, LVH progressively decreased in all 3 groups, but there was an additional 28% reduction in the dual therapy group (P<0.05) 70 despite similar blood pressure reduction. A 3 rd small trial compared imadpril (2.5 mg daily) with placebo in 30 hemodialysis patients.…”
Section: Interventions To Regress Lvhmentioning
confidence: 85%
“…Echocardiogram findings such as LV systolic dysfunction, 5 LVH 6 and valvular calcification 7 are associated with increased mortality in dialysis patients. Intervention with medications has been shown to slow down the progression or regress the pathological echocardiogram findings (such as ACEI or ARB for LVH 8 and sevelamer for valvular calcification 9 ). However, to date, there are no studies that show improved mortality from these medications in dialysis patients with these specific echocardiogram findings (except carvedilol for dilated cardiomyopathy in a single study 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…For adult hypertensive human patients, Devereux et al 25 reported reduction of the LVM after 12 and 24 months of treatment with losartan. Suzuki et al 26 reported that, for diabetic adults with end-stage renal disease undergoing hemodialysis, combined therapy with ACE inhibitors and AT 1 receptor antagonists was more effective in reducing the LVM after 6 and 12 months of treatment than was single therapy with ACE inhibitors or AT 1 receptor antagonists alone. It is noteworthy that the experimental studies with rats suggested that the heart mass reduction could become evident much earlier than commonly described, which supports our observation.…”
Section: Discussionmentioning
confidence: 99%